Pengukuran Faktor yang Berpengaruh terhadap Motivasi Ibu Hamil Mengikuti Prenatal Yoga - Siti Khoiriyah; Mutiara Ayu Muthiatulsalimah; Herjanti Herjanti (Jurnal Kebidanan Harapan Ibu Pekalongan, 2024)
This lack of motivation to follow pregnant mother prenatal yoga is due to the lack of health promotion, lack of facilities, the lack support of pregnant mother to follow prenatal yoga like family and hausband support. The purpose of this study was to know the direct and indirect influence to the motivation of pregnant mother following prenatal yoga in BPS Erie Depok Year 2017. The method used in this research was a quantitative approach and the design was cross-setional. The samples used were 60 pregnant as respondents. The analytical method used was SEM using SmartPLS 2.0 and SPSS 20. The results of this research showed that the pregnant mother motivation to follow a prenatal yoga influenced by health promotion (21.61%), availability of facilities (29.11%), the role of the midwife (14.38%) and the role of husband (14.63%). The direct effect of pregnant mother motivation as 79.7% and the indirect effect as 1.4% and total direct and indirect influence as 8.11%. The result of this research conclude that availability of facilities is a dominant factor greatly affects the motivation of pregnant mother to follow a prenatal yoga.